Value Chain Upgrading: Evidence from the Singaporean Aquaculture Industry - Lim, Guanie (2017)
This paper examines the Singaporean aquaculture industry using an integrated perspective that draws on the global value chain and global production network approaches. The paper focuses especially on the upgrading efforts of the fish farming firms operating at the industry’s upstream node. Based on research and qualitative personal interviews with firms involved in the Singaporean aquaculture industry, this paper argues that the city-state’s wider institutional context – dirigisme in governing the utilization of land and sea space, and commitment to a liberalized trade regime to feed its populace – complicates the upgrading efforts of the fish farming firms. Notwithstanding the inherent complexities of economic upgrading per se, such findings prove that while upgrading is an effort driven by the firm and its cohort of stakeholders, the effort is unlikely to succeed if the broader institutional and regulatory environment that the firms are embedded in is not conducive.